Enzyme-mimic CeO2-based multi-active-site catalyst, preparation method and application thereof, electrolytic tank and battery

By anchoring ultrafine X nanoclusters and X-doped Ni2P nanoparticles on CeO2 nanorods, a multi-active-site catalyst was prepared, which solved the problems of high cost and insufficient activity of catalytic materials in the prior art, and achieved high-efficiency electrocatalytic ammonia production and improved OER performance.

CN121344668AActive Publication Date: 2026-01-16SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202511884095.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-01-16
Estimated Expiration
2045-12-15

AI Technical Summary

Technical Problem

Existing commercially available catalytic materials are expensive and lack sufficient activity, resulting in low power, low ammonia production current, low ammonia yield, and poor stability of zinc nitrate batteries, making it difficult to achieve efficient electrocatalytic ammonia production and OER reactions.

Method used

Anchoring ultrafine X (X=Fe, Co, Cu or Mn) nanoclusters and X-doped Ni2P nanoparticles on CeO2 nanorods to form a multi-active-site catalyst was prepared by a one-step hydrothermal method and sodium hypophosphite phosphating reaction, optimizing the adsorption configuration and reaction rate of nitrogen-containing intermediates.

Benefits of technology

It achieves highly efficient electrocatalytic ammonia production from nitrate and OER performance, significantly improving ammonia yield and Faraday efficiency, increasing battery power density, and enhancing stability and economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121344668A_ABST
    Figure CN121344668A_ABST
Patent Text Reader

Abstract

The invention relates to an enzyme-mimic CeO2-based multi-active-site catalyst, a preparation method and application thereof, an electrolytic tank and a battery. CeO2 nanorods are synthesized through hydrothermal and high-temperature pyrolysis methods, and then metal ions are anchored to the surfaces of the CeO2 nanorods through strong interaction of carriers; metal nanoclusters and nanoparticles with specific sizes are synthesized, and then chemical vapor deposition reaction is performed through sodium hypophosphite, so that the bionic nano-enzyme electrocatalyst with multiple active sites is obtained. The multi-active-site catalytic material provided by the invention has high selectivity of ammonia production from nitrate radicals, ammonia production efficiency and Faraday efficiency when being used as a cathode. When the RuO2 is used as an anode, in an alkaline water electrolysis reaction, when the current density is 50 mA / cm < 2 >, the overpotential is 288 mV, which is far better than that of commercial RuO2. Based on excellent oxidation and reduction performance, the zinc nitrate battery has high power density, high ammonia yield and good charge-discharge cycle stability, and nitrate removal, ammonia production and power supply can be achieved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical catalyst technology, specifically to the development of an enzyme-inspired CeO2-supported X (X=Fe, Co, Cu or Mn) nanoclusters and X (X=Fe, Co, Cu or Mn) doped nickel phosphide nanoparticles multi-active-site catalyst, its preparation method and application. Background Technology

[0002] Electrochemical nitrate-to-ammonia production driven by green electricity is a sustainable ammonia production pathway that avoids the high energy consumption and high carbon dioxide emissions of the traditional Haber-Bosch process. However, the electrocatalytic nitrate-to-ammonia process involves octetrate and nonaproton reactions, and its oxygen evolution reaction (OER) at the anode involves a complex four-electron transfer process, resulting in slow kinetics and a high overpotential (1.23 eV), which severely restricts its industrial application. To improve the efficiency of electrocatalytic ammonia production and reduce the energy barrier of the reaction, it is urgent to develop low-cost, efficient, and stable multi-active-site functional catalytic materials to address the high adsorption and activation energies caused by kinetic mismatch between single active sites and different intermediates.

[0003] Currently, commercially available catalytic materials are mainly platinum group metals and their oxides. However, the scarcity of precious metal materials and their high cost limit their large-scale practical application. In recent years, research on low-cost catalytic materials has mainly focused on non-precious metal sulfides, nitrides, and phosphides, which often exhibit excellent platinum-like electrocatalytic performance. However, the specific electronic structure and physicochemical properties of a single crystal phase limit their application in the field of electrocatalysis. It has been reported that the electronic structure of Ni2P can be effectively controlled by doping with the transition metal element Fe, and it can participate in electrocatalytic reactions as a new active site. Patent publication number CN109201094 B discloses a porous nanoflower-like Ni2P material applied to OER. Patent publication number CN 113061929A discloses a three-dimensional ultrathin nanosheet material doped with nickel iron phosphide applied to whole water splitting.

[0004] However, the following problems still exist in the practical application of this Ni2P metal doped material: First, a suitable substrate has not been found, which makes its processing and usage costs high; second, the material has insufficient activity, and the problems of low power, low ammonia production current, low ammonia yield and poor stability of zinc nitrate batteries have not been well solved.

[0005] Therefore, in order to meet the requirements of high ammonia production Faradaic efficiency, high ammonia yield and good charge-discharge stability of zinc nitrate batteries, it is urgent to develop a nanoenzyme electrocatalyst with excellent electrocatalytic nitrate reduction performance and OER activity. Summary of the Invention

[0006] Therefore, the technical problem to be solved by this invention is to overcome the shortcomings of the prior art, thereby providing an enzyme-inspired CeO2-based multi-active-site catalyst, its preparation method and application, as well as an electrolytic cell and a battery. Specifically, this invention anchors ultrafine X (X=Fe, Co, Cu or Mn) nanoclusters and X (X=Fe, Co, Cu or Mn)-doped Ni2P nanoparticles on a CeO2 substrate, exhibiting excellent nitrate ammonia production and OER performance, as well as excellent zinc nitrate battery performance.

[0007] To achieve the above objectives, the present invention first provides an enzyme-inspired CeO2-based multi-active-site catalyst, wherein CeO2 nanorods are supported with X nanoclusters and X-doped Ni2P nanoparticles, wherein X is Fe, Co, Cu or Mn.

[0008] In the preferred embodiment, the total mass of X is 0.1% to 50% of CeO2; the mass of Ni2P is 0.1% to 50% of CeO2.

[0009] This invention also provides a method for preparing an enzyme-inspired CeO2-based multi-active-site catalyst, comprising the following steps: Step 1: Mix cerium salt with ammonia water evenly, and obtain CeO2 nanorods by one-step hydrothermal method, centrifugal washing, vacuum drying, and air atmosphere heat treatment. Step 2: Stir the aqueous solutions of X salt, nickel salt, reducing material and template material evenly to obtain a mixed solution; wherein, X salt is an iron salt, cobalt salt, copper salt or manganese salt; Step 3: By adding the CeO2 nanorods obtained in Step 1 to the mixed solution in Step 2, the strong interaction between the metal and the support is used to anchor the metal ions onto the CeO2 nanorods to form a precursor. Step 4: The precursor synthesized in Step 3 is subjected to sodium hypophosphite phosphating reaction to obtain CeO2 nanorods supported on X nanoclusters and X-doped Ni2P nanoparticles. When iron salts are used in step 2, a multi-active-site Fe-Fe composite is obtained, consisting of CeO2 nanorods supporting Fe nanoclusters and Fe-doped Ni2P nanoparticles. x Ni 2-x P / CeO2 biomimetic nano-enzyme electrocatalyst; Alternatively, when cobalt salts are used in step 2, a multi-active-site Co-Co structure is obtained, consisting of CeO2 nanorods supporting Co nanoclusters and Co-doped Ni2P nanoparticles. x Ni 2-x P / CeO2 biomimetic nano-enzyme electrocatalyst; Alternatively, when copper salt is used in step 2, a Cu-Cu composite with multiple active sites is obtained, consisting of CeO2 nanorods supporting Cu nanoclusters and Cu-doped Ni2P nanoparticles.x Ni 2-x P / CeO2 biomimetic nano-enzyme electrocatalyst; Alternatively, when manganese salt is used in step 2, a multi-active-site Mn-Mn composite is obtained, consisting of CeO2 nanorods supporting Mn nanoclusters and Mn-doped Ni2P nanoparticles. x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalyst.

[0010] In the preferred embodiment, in step 1, the cerium salt is at least one of nitrate, chloride, or sulfate; and the synthesis of CeO2 nanorods in step 1 is carried out in an alkaline environment at pH = 10-14. The hydrothermal reaction temperature is 100~200 degrees Celsius, lasting 5~30 hours; the air atmosphere heat treatment temperature is 300~700 degrees Celsius, lasting 1~10 hours. In step 2, the iron salt and nickel salt are at least one of nitrate, chloride, or sulfate; The reducing agent is at least one of sodium citrate, glucose, ethylene glycol, and glycerol; the template material is at least one of hexamethylenetetramine, polyvinylpyrrolidone, and ethylenediamine. In step 4, the phosphating reaction is carried out at a temperature of 200-300 degrees Celsius for 1-5 hours.

[0011] In the preferred embodiment, the amount of reducing material added is 0.1% to 50% of the cerium salt; the amount of template material added is 1 to 10 times the cerium salt; the amount of sodium hypophosphite added is 1% to 300% of the cerium oxide; the amount of nickel salt added is 1 to 10 times the cerium oxide; and the amount of X salt added is 1% to 300% of the cerium oxide.

[0012] The multi-active site Fe-Fe of the present invention x Ni 2-x The mechanism of some reaction steps in the preparation method of P / CeO2 biomimetic nanozyme electrocatalyst is explained as follows: (1) In step 1 above, under the premise of mixing cerium salt and ammonia water, an alkaline environment (pH: 10~14) can induce crystal directional growth and obtain a rod-shaped structure, that is, the CeO2 nanorod of the present invention is obtained. (2) In step 3 above, after placing the iron salt and nickel salt in a mixture containing CeO2 nanorods, the CeO2 surface can be activated and metal ions can be adsorbed under the action of reducing material and template material. The key is to control the ratio of metal ions, so as to achieve the controllable growth of nanoclusters and nanoparticles.

[0013] (3) In step 4 above, the prepared cerium-based X nanoclusters and X-doped Ni2P nanoparticle composite material are subjected to a vapor deposition reaction with sodium hypophosphite to obtain multi-active-site XX. x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalyst.

[0014] According to the multi-active-site Fe-Fe of the present invention x Ni 2-x The preparation method of P / CeO2 biomimetic nanozyme electrocatalyst optimizes the adsorption configuration of nitrogen-containing intermediates and the rate of water splitting by designing multiple active sites, thereby reducing the energy barrier for nitrate reduction to ammonia and increasing the hydrogenation rate of nitrogen-containing intermediates, thus improving the selectivity and yield of electrocatalytic ammonia production.

[0015] The present invention further provides an application of the above-mentioned enzyme-mimicking CeO2-based multi-active-site catalyst as a cathode material for the electrolysis of nitrate to produce ammonia.

[0016] The present invention further provides an application of the above-mentioned enzyme-mimicking CeO2-based multi-active-site catalyst as an anode material for an alkaline electrolyzer.

[0017] The present invention further provides a nitrate-based electrolytic cell, which includes an anode material, a cathode material and a reference electrode; the cathode material adopts the above-mentioned enzyme-inspired CeO2-based multi-active-site catalyst, the reference electrode is a mercury / mercury oxide electrode, and the anode material is a Pt sheet. The present invention further provides an alkaline electrolytic cell, comprising an anode material, a cathode material, and a reference electrode; the anode material is the above-mentioned enzyme-inspired CeO2-based multi-active-site catalyst, the reference electrode is a mercury / mercury oxide electrode, and the cathode material is a Pt sheet.

[0018] The present invention further provides a zinc nitrate battery, which includes a positive electrode material and a negative electrode material. The positive electrode material adopts the above-mentioned enzyme-mimicking CeO2-based multi-active-site catalyst, and the negative electrode material is a zinc sheet.

[0019] The present invention, employing the above-described technical solution, has the following advantages compared to the prior art: 1. This invention uses CeO2 nanorods as a substrate. Metal ions in the mixed solution are anchored to the surface of the CeO2 nanorods through strong interactions with the metal support. With the help of reducing agents and template materials, ultrafine X nanoclusters and X-doped Ni2P nanoparticles with high activity, high stability, low cost, and controllable morphology are synthesized. Specifically, Fe-Fe x Ni 2-x P / CeO2, Co-Co x Ni 2-x P / CeO2, Cu-Cux Ni 2-x P / CeO2 and Mn-Mn x Ni 2-x P / CeO2.

[0020] 2. The multi-active-site ultrafine X (X=Fe, Co, Cu or Mn) nanoclusters and X (X=Fe, Co, Cu or Mn) doped Ni2P nanoparticles prepared by this invention effectively increase the number of active centers, optimize the adsorption configuration of nitrogen-containing intermediates, and reduce the reaction barrier for electrocatalytic ammonia production from nitrate.

[0021] 3. The multi-active-site Fe-Fe provided by this invention x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalysts can be used as cathode materials for the electrolysis of nitrate to ammonia, enabling industrial-scale ammonia production at high current densities. In 1 mol / L KOH and 0.5 mol / L KNO3 solutions, at -0.7 V vs. RHE potential, a Faradaic efficiency of 91.2% and a high efficiency of 43.76 mgh are achieved. -1 cm -2 ammonia yield.

[0022] 5. The multi-active-site Fe-Fe provided by this invention x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalysts can be used as anode materials in alkaline electrolyzers. In the OER reaction, at a current density of 50 mA / cm²... 2 At that time, the overpotential was only 288 mV, which is far superior to the commercially available precious metal material RuO2.

[0023] 6. The multi-active-site Fe-Fe provided by this invention x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalysts can be used as positive electrode materials in zinc nitrate batteries, simultaneously achieving ammonia production from nitrate and electricity output. Notably, the assembled battery achieves a maximum power density of 21.1 mW / cm². 2 Therefore, the present invention provides a multi-active-site Fe-Fe x Ni 2-x P / CeO2 biomimetic nanozyme electrocatalyst material has significant economic value.

[0024] 7. Similarly, the Co-Co material synthesized in this invention... x Ni 2-x P / CeO2, Cu-Cu x Ni 2-x P / CeO2 and Mn-Mn x Ni2-x P / CeO2 also has the properties of Fe-Fe x Ni 2-x Similar properties to P / CeO2 will be compared with data in the following text. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 The X-ray diffraction (XRD) patterns are shown for Example 1, Comparative Example 1, Comparative Example 2, experimental sample CeO2, standard card Ni2P (PDF#21-0590), and standard card CeO2 (PDF#34-0394) of this invention. Figure 2 The multi-active-site Fe-Fe provided in Example 1 of this invention x Ni 2-x High-resolution transmission electron microscopy (HR-TEM) image of the P / CeO2 biomimetic nanoenzyme electrocatalyst; Figure 3 Linear sweep voltammetry (LSV) curves of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention in a mixed solution of 1 mol / L KOH and 0.5 mol KNO3; Figure 4 The multi-active-site Fe-Fe provided in Example 1 of this invention x Ni 2-x P / CeO2 biomimetic nanozyme electrocatalyst for electrocatalytic ammonia production from nitrate at -0.4 V vs. RHE potential for 16 cycles: Faradaic efficiency and ammonia yield. Figure 5 The LSV diagrams for Example 1, Comparative Example 1, and Comparative Example 2 of the present invention in 1 mol / L KOH are shown below. Figure 6 The multi-active-site Fe-Fe provided in Example 1 of this invention x Ni 2-x Discharge curves and corresponding power density plots of zinc nitrate batteries assembled with P / CeO2 biomimetic nanoenzyme electrocatalysts. Figure 7 The multi-active-site Fe-Fe provided in Example 1 of this invention x Ni 2-x A zinc nitrate battery assembled with a P / CeO2 biomimetic nanoenzyme electrocatalyst operates at 3 mA / cm².2 Discharge and charge diagrams under constant current density. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to the accompanying drawings, tables, and specific experimental schemes. Those skilled in the art can easily understand the technical solution of the present invention based on this specification. It is also worth noting that, unless otherwise specified, all methods are conventional, and the instruments and materials mentioned are commercially available.

[0028] The endpoint values ​​of the ranges described in this description are not limited to the precise ranges or values; these ranges should be understood as including or approximating the values ​​within these ranges. For a specific synthetic scheme, one or more schemes should be obtained by combining individual point values ​​within each range, and these values ​​should be considered as specifically disclosed in this patent.

[0029] Example 1: A low-cost multi-active-site Fe-Fe x Ni 2-x The preparation method of P / CeO2 biomimetic nano-enzyme electrocatalyst includes the following steps: CeCl3·7H2O was used as the material for synthesizing CeO2 nanorods, and NaH2PO2·H2O was used as the raw material. 25% NH3·H2O was selected as the modifier for the synthesis of CeO2 nanorods, with the amount of NH3·H2O being 20% ​​of CeCl3·7H2O. Ni(NO3)2·6H2O and Fe(NO3)3·6H2O were selected as the materials for preparing Fe-Fe... x Ni 2-x P / CeO2 biomimetic nanoenzyme electrocatalyst raw material.

[0030] Preparation of CeO2 nanorods: The raw materials were prepared by mass percentage: CeCl3·7H2O 6.93%, ultrapure water 74.45%, and NH3·H2O 18.62%. After stirring at 1000 rpm for 1 hour, the mixture was transferred to a hydrothermal reactor and kept at 180 degrees Celsius for 24 hours. The mixture was then washed 5 times by centrifugation with a mixture of ultrapure water and ethanol (volume ratio 1:1). After vacuum drying at 60 degrees Celsius, the mixture was transferred to a muffle furnace and heat-treated at 600 degrees Celsius for 4 hours to obtain CeO2 nanorods.

[0031] Fe-Fe x Ni 2-x Synthesis of P / CeO2 biomimetic nanoenzyme electrocatalyst: Fe-Fe x Ni 2-xThe specific details of the synthesis of the P / CeO2 biomimetic nanoenzyme electrocatalyst are as follows: 0.6684 g of the prepared CeO2 nanorods were dispersed in 30.0 mL of ultrapure water. Then, 0.291 g of sodium citrate, 4.2 g of hexamethylenetetramine, 2.9 g of Ni(NO3)2·6H2O, and 0.404 g of Fe(NO3)3·6H2O were added to the solution, and the mixture was stirred at 600 rpm for 30 minutes to form a homogeneous solution. Subsequently, the mixed solution was heated in an oil bath at 80°C for 5 hours with stirring at 400 rpm. The resulting precipitate was washed three times sequentially by centrifugation with ultrapure water and anhydrous ethanol, and then dried in a vacuum oven at 60°C to obtain FeNi / CeO2. 0.15 g of FeNi / CeO2 and 0.5 g of NaH2PO2·H2O were placed separately in independent corundum magnetic boats. NaH₂PO₂·H₂O was located upstream of the dual-temperature zone tube furnace, while FeNi / CeO₂ was located downstream. Under a nitrogen atmosphere, the temperature was increased to 300°C at a rate of 2°C / min and held for 2 hours, then naturally cooled to room temperature to obtain multi-active-site Fe-Fe x Ni 2- x P / CeO2 electrocatalytic materials.

[0032] The multi-active-site Fe-Fe prepared in this embodiment x Ni 2-x X-ray diffraction (XRD) pattern of P / CeO2 biomimetic nanozyme electrocatalyst as follows: Figure 1 As shown in the figure. The prepared Fe-Fe can be observed from the figure. x Ni 2-x The diffraction peaks of the P / CeO2 biomimetic nanozyme electrocatalyst correspond one-to-one with those of the experimental CeO2. Compared with the standard cards CeO2 (PDF#34-0394) and Ni2P (PDF#21-0590), no other extra peaks were found, and no Fe-based or Ni-based diffraction peaks were observed, indicating the successful preparation of ultrafine Fe nanoclusters and Fe-doped Ni2P nanoparticles; simultaneously, through... Figure 2 HR-TEM images show that the 0.195 nm interplanar spacing corresponds to the (111) crystal plane of CeO2. The surface of the CeO2 nanorods is covered with ultrafine Fe nanoclusters with a size of about 1.8 nm and nanoparticles with a size of about 10.0 nm. The 0.208 nm interplanar spacing of the nanoparticles shows a certain lattice shrinkage compared to the 0.222 nm interplanar spacing of the (111) crystal plane of Ni2P, indicating lattice strain caused by Fe incorporation into the Ni2P lattice. The surface layer is amorphous CeO2.

[0033] Example 2: Electrocatalytic nitrate reduction test: Working electrode preparation: 2.0 mg of the catalyst material prepared in Example 1 was dispersed in a mixed solution containing 200 μL of perfluorosulfonic acid polymer (Nafion 117), 1.6 mL of water, and 3.2 mL of isopropanol, and then sonicated for 1 hour to obtain a homogeneous slurry. The slurry was then uniformly coated onto a 0.2 cm thick surface. 2 Clean carbon paper with a loading of 1 mg / cm³ 2 It is dried using an infrared lamp and then used as a working electrode.

[0034] The performance of the working electrode in Example 1 was tested using a CHI760E electrochemical workstation from Shanghai Chenhua Instruments Co., Ltd. A three-electrode H-type electrolytic cell was used, with the anode and cathode chambers separated by an anion exchange membrane (FAA-3-PK-130). Hg / HgO was used as the reference electrode, a Pt sheet as the counter electrode, and carbon paper coated with the prepared catalytic material as the working electrode. The electrolyte was a 30 mL mixture of 1.0 mol / L KOH and 0.5 mol / L KNO3. All electrochemical tests were conducted under Ar purging conditions. Before the electrocatalytic nitrate reduction test, the electrolyte was purged with Ar gas for 30 minutes to remove air from the solution.

[0035] The specific details of the test were as follows: First, cyclic voltammetry (CV) was used to activate the device to stability by performing 50 cycles from +0.1V to -1.0V vs. RHE. Then, linear voltammetry was used to test the device from 0V to -1.0V vs. RHE at a scan rate of 5 mV / s, and the ammonia current density was recorded. Figure 3 The ammonia current density is shown in Table 1. At a potential of -0.5V vs. RHE, the ammonia current density reaches 287.5 mA / cm². 2 Finally, the chronoamperometry method was used to test the ammonia production performance under constant voltage reduction for 30 minutes at different potentials. The electrolyte after the reaction was collected, and the corresponding Q values ​​were recorded.

[0036] The measured potential is corrected to that of a reversible hydrogen electrode using the following formula: E RHE = E Hg / HgO + 0.059*pH +0.098 V (1); E Hg / HgO E represents the actual implemented electric potential. RHE This represents the relatively reversible hydrogen electrode potential.

[0037] Ammonia product detection: The collected electrolyte was first diluted with a mixed solution of 1.0 mol / L KOH and 0.5 mol / L KNO3, then neutralized and diluted again with a mixed solution of 0.5 mol / L H2SO4 and 0.5 mol / L KNO3. The ammonia concentration was then quantitatively determined using the indophenol blue method. Specifically, the absorption spectrum of the solution in the range of 500 nm to 800 nm and the absorbance at 655 nm were measured using a UV-3900 UV-Vis spectrophotometer manufactured by Hitachi, Japan. The concentration was then quantified using a standard curve for ammonia. Table 2 below shows the ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material for the production of ammonia from nitrate at -0.7 V vs. RHE. The ammonia Faradaic efficiency reached 91.2%, and the ammonia yield was 43.5 mg h⁻¹. -1 cm -2 It exhibits excellent electrocatalytic performance in the production of ammonia from nitrate.

[0038] Example 3: Unlike Example 2, Fe-Fe x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst underwent 16 cycles of stability testing at -0.4V vs. RHE. Figure 4 The results showed that the ammonia production Faraday efficiency of the catalytic material remained at around 90%, further demonstrating good stability.

[0039] Example 4: Unlike Example 2, the prepared catalyst was used as the anode in the electrocatalytic OER reaction (oxygen evolution reaction).

[0040] The specific details are as follows: Based on Fe-Fe x Ni 2-x The P / CeO2 anode working electrode was prepared using the same method as the cathode working electrode described above. A single electrolytic cell with a three-electrode system was used, with Hg / HgO as the reference electrode and a Pt sheet as the counter electrode. The Fe-Fe alloy prepared in Example 2 above... x Ni 2-x A carbon paper coated with P / CeO2 biomimetic nanoenzyme electrocatalyst was used as the working electrode anode. The electrolyte was 100 mL of 1.0 mol / L KOH solution. Before electrocatalytic OER testing, activation to stability was achieved by cyclic voltammetry (CV) from +1.0 V to 1.8 V vs. RHE for 50 cycles. Subsequently, linear voltammetry was performed at a scan rate of 5 mV / s, with the scan potential range from 1.0 V to 1.8 V vs. RHE. The recorded OER current density curve was... Figure 5 The catalyst operates at a current density of 50 mA / cm². 2With an overpotential of only 288mV, its performance is far superior to that of commercially available RuO2, indicating excellent OER performance.

[0041] Example 5: Applications of zinc nitrate batteries: Battery assembly: Fe-Fe x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst exhibits excellent nitrate-to-ammonia and OER performance. Following the method described in Example 2 above, a working electrode was prepared as the positive electrode, and a 5 mm thick zinc sheet was prepared as the negative electrode. The electrolyte for the positive electrode was a mixed solution of 30 mL of 1.0 mol / L KOH and 0.5 or 1.0 mol / L KNO3, while the electrolyte for the negative electrode was a mixed solution of 1.0 mol / L KOH and 0.02 mol / L (CH3COO)2Zn. The positive and negative electrodes were separated by an anion exchange membrane (FAA-3-PK-130).

[0042] The performance of the zinc nitrate battery was first tested using a CHI760E electrochemical workstation. Its discharge curve and power density were then analyzed. Figure 6 In 1.0 M KOH and 0.5 M potassium nitrate solutions, Fe-Fe x Ni 2-x The P / CeO2 biomimetic nano-enzyme electrocatalyst boasts a maximum power density of 21.1 mW / cm². 2 .

[0043] Example 6: Zinc nitrate battery charge / discharge stability test: The difference between this embodiment and Embodiment 5 is that the assembled zinc nitrate battery is operated at 3 mA / cm. 2 The following long-term charge-discharge cycle tests were conducted for evaluation, and the operating curves were recorded as follows: Figure 7 As shown, the cycle stability reached 8 hours.

[0044] Example 7: A low-cost multi-active-site Co-Co x Ni 2-x The preparation method of P / CeO2 biomimetic nano-enzyme electrocatalyst includes the following steps: Unlike Example 1, in Example 7, an equimolar amount of Co(NO3)2·6H2O was added to the mixed solution instead of Fe(NO3)3·6H2O, and the rest of the preparation process and steps were the same as in Example 1.

[0045] Example 8: The sample from Example 7 was subjected to electrocatalytic nitrate reduction testing as described in Example 2, and the ammonia current density was recorded. The ammonia current densities at different potentials are shown in Table 1. At a potential of -0.7V vs. RHE, the current density approaches 500 mA / cm². 2 To achieve industrial-grade current density standards, the sample from Example 7 was further tested at different potentials using the same method as in Example 2, with constant current reduction of nitrate to ammonia. The ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material at different potentials were recorded. As shown in Table 2 below, the sample from Example 7 achieved an ammonia Faradaic efficiency of 90.4% at a voltage of -0.7V vs. RHE, with an ammonia yield of 42.7 mg / h. -1 cm -2 .

[0046] Furthermore, the electrocatalytic OER performance of the sample from Example 7 was tested according to the method described in Example 4. As shown in Table 3, the sample from Example 7 performed at 50 mA / cm². 2 Its overpotential is 296 mV, and its actual OER performance is better than that of commercially available RuO2.

[0047] Furthermore, the sample from Example 7 was assembled into a zinc nitrate battery according to the method of Example 5, except that the sample from Example 7 was used as the positive electrode of the battery. In a 1.0 M KOH and 0.5 M potassium nitrate solution, the maximum power density of the sample from Example 7 was 19.3 mW / cm³. 2 .

[0048] Example 9: A low-cost, multi-active-site Cu-Cu x Ni 2-x Preparation method of P / CeO2 biomimetic nanoenzyme electrocatalyst. Unlike Example 1, Example 9 uses an equimolar amount of Cu(NO3)2·3H2O to replace Fe(NO3)2·6H2O in the mixed solution, while the rest of the preparation process and steps are the same as in Example 1.

[0049] Example 10: The sample from Example 9 was subjected to electrocatalytic nitrate reduction testing as described in Example 2, and the ammonia current density was recorded. As shown in Table 1, the sample from Example 9 exhibited the highest ammonia current density of 654.3 mA / cm² at a potential of -0.7 V vs. RHE. 2Furthermore, the sample from Example 9 was subjected to constant-current nitrate reduction to ammonia production at different potentials, following the method described in Example 2. The ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material at different potentials were recorded. As shown in Table 2, at a voltage of -0.7 V vs. RHE, its ammonia production Faradaic efficiency exceeded 95%, and the ammonia yield was 47.6 mg h⁻¹. -1 cm -2 .

[0050] Furthermore, the electrocatalytic OER performance of the sample from Example 9 was tested according to the method described in Example 4. As shown in Table 3, the sample from Example 9 achieved an OER performance of 50 mA / cm². 2 The overpotential was 373 mV. This indicates that Example 9 could not simultaneously achieve both excellent electrocatalytic nitrate to ammonia production and OER reactions.

[0051] Furthermore, the sample from Example 9 was assembled into a zinc nitrate battery according to the method of Example 5. The difference from Example 5 is that the sample from Example 9 was used as the positive electrode of the battery. In a 1.0 M KOH and 0.5 M potassium nitrate solution, the maximum power density of the sample from Example 9 reached as high as 27.3 mW / cm³. 2 However, its charge / discharge performance is limited by the poor OER performance of the sample in Example 9.

[0052] Example 11: A low-cost multi-active-site Mn-Mn x Ni 2-x Preparation method of P / CeO2 biomimetic nanoenzyme electrocatalyst.

[0053] Unlike Example 1, in Example 11, an equimolar amount of Mn(NO3)2·4H2O was added to the mixed solution instead of Fe(NO3)2·6H2O, and the rest of the preparation process and steps were the same as in Example 1.

[0054] Example 12: The sample from Example 11 was subjected to electrocatalytic nitrate reduction testing as described in Example 2, and the ammonia current density was recorded. As shown in Table 1, the current density of Example 11 at a potential of -0.7 V vs. RHE reached -563.7 mA / cm². 2 To achieve industrial-grade current density standards, the sample from Example 11 was further tested at different potentials using the same method as in Example 2, with constant current reduction of nitrate to ammonia. The ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material at different potentials were recorded. As shown in Table 2, the sample from Example 11 exhibited an ammonia Faradaic efficiency of 87.8% and an ammonia yield of 40.8 mg h⁻¹ at a voltage of -0.7 V vs. RHE. -1 cm-2 .

[0055] Furthermore, the electrocatalytic OER performance of the sample from Example 11 was tested according to the method described in Example 4. As shown in Table 3, the sample from Example 11 performed at 50 mA / cm². 2 The overpotential is 298 mV.

[0056] Furthermore, the sample from Example 11 was assembled into a zinc nitrate battery according to the method of Example 5. The difference from Example 5 is that the sample from Example 11 was used as the positive electrode of the battery. In a 1.0 M KOH and 0.5 M potassium nitrate solution, the sample from Example 11 achieved a maximum power density of 15.7 mW / cm³. 2 .

[0057] Comparative Example 1: A method for preparing a single-active-site Ni2P / CeO2 electrocatalytic material includes the following steps: Unlike Example 1, Fe(NO3)2·6H2O was not added in Comparative Example 1, but the rest of the preparation process and steps were the same as in Example 1.

[0058] Furthermore, XRD testing will be performed on Example 1. Figure 1 It can be seen that the XRD diffraction peaks of the Ni2P / CeO2 electrocatalytic material prepared by the present invention correspond one-to-one with the peaks of the experimental CeO2. Compared with the standard cards CeO2 (PDF#34-0394) and Ni2P (PDF#21-0590), no other extra peaks were found, and no Ni-based diffraction peaks were observed, indicating that Ni2P nanoparticles were successfully prepared.

[0059] Furthermore, the sample of Comparative Example 1 was subjected to electrocatalytic nitrate reduction testing according to the method of Example 2. As shown in Table 1, the current density of the sample of Comparative Example 1 at a potential of -0.7V vs. RHE was only -337.5mA / cm². 2 Furthermore, the sample of Comparative Example 1 was subjected to constant current reduction of nitrate to ammonia at different potentials, as in Example 2. The ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material at different potentials were recorded. As shown in Table 2, the sample of Comparative Example 1, at a voltage of -0.7 V vs. RHE, had an ammonia Faradaic efficiency of only 78.9% and an ammonia yield of 35.8 mg h⁻¹. - 1 cm -2 The ammonia yield and Faraday efficiency of the sample in Comparative Example 1 were much lower than those of the catalyst with multiple active sites, indicating the limitations of this single active site in the multi-step electrochemical reaction for ammonia production.

[0060] Furthermore, the electrocatalytic OER performance of the sample from Comparative Example 1 was tested according to the method described in Example 4. As shown in Table 3, the sample from Comparative Example 1 achieved an OER performance of 50 mA / cm². 2 The overpotential is 340 mV. Its poor OER performance further verifies the superiority of multi-active-site catalysts.

[0061] Comparative Example 2: A method for preparing Fe / CeO2 electrocatalytic material includes the following steps: Unlike Example 1, Comparative Example 2 did not add Ni(NO3)2·6H2O, but the rest of the preparation process and steps were the same as in Example 1.

[0062] Furthermore, XRD testing will be performed on Example 2. Figure 1 It can be seen that the XRD diffraction peaks of the Fe / CeO2 electrocatalytic material prepared by the present invention correspond one-to-one with the peaks of the experimental CeO2. Compared with the standard cards CeO2 (PDF#34-0394) and Ni2P (PDF#21-0590), no other extra peaks were found, and no Fe-based diffraction peaks were observed, indicating that the ultrafine Fe nanoclusters were successfully prepared.

[0063] Furthermore, the sample of Comparative Example 2 was subjected to electrocatalytic nitrate reduction testing according to the method of Example 2. As shown in Table 1, the current density of the sample of Comparative Example 2 at a potential of -0.7V vs. RHE was only -265.1mA / cm². 2 Furthermore, the sample of Comparative Example 2 was subjected to constant current reduction of nitrate to ammonia at different potentials, following the method described in Example 2. The ammonia yield and ammonia Faradaic efficiency of the electrocatalytic material at different potentials were recorded. As shown in Table 2, the sample of Comparative Example 2, at a voltage of -0.7 V vs. RHE, exhibited an ammonia Faradaic efficiency of 75.3% and an ammonia yield of 28.5 mg h⁻¹. -1 cm -2 .

[0064] Furthermore, the electrocatalytic OER performance of the sample from Comparative Example 2 was tested according to the method described in Example 4. As shown in Table 3, the sample from Comparative Example 2 performed at 50 mA / cm². 2 The overpotential exceeds 500 mV, which is greater than the overpotential of the multi-active-site biomimetic nanoenzyme electrocatalyst in Example 1.

[0065] The above examples and comparative examples demonstrate the versatility of synthesizing this multi-active-site biomimetic nanozyme electrocatalyst, encompassing nanoclusters and nanoparticles. They also highlight the advantages of this multi-active-site biomimetic nanozyme electrocatalyst in the synergistic tandem catalysis of nitrate-to-ammonia electrocatalysis. Furthermore, electrochemical performance tests and zinc nitrate battery tests confirm the superior performance of the multi-active-site components in the tandem ammonia production and OER reactions, providing a good demonstration for achieving highly efficient and stable biomimetic nanozyme electrocatalysts.

[0066] Table 1:

[0067] Table 2:

[0068] Table 3:

[0069] The results of sample testing obtained from the different embodiments and comparative examples described above are further explained below with reference to the accompanying drawings.

[0070] pass Figure 1 It can be seen that the multi-active-site Fe-Fe prepared using this invention... x Ni 2-x The XRD diffraction peaks of the P / CeO2 biomimetic nanoenzyme electrocatalyst correspond one-to-one with the peaks of the experimental CeO2. Compared with the standard cards CeO2 (PDF#34-0394) and Ni2P (PDF#21-0590), no other extra peaks were found, and no Fe-based or Ni-based diffraction peaks were observed, indicating that ultrafine Fe nanoclusters and Fe-doped Ni2P nanoparticles were successfully prepared.

[0071] pass Figure 2 It can be seen that the multi-active-site Fe-Fe prepared using the method described in this invention... x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst exhibits a structure in which Fe nanoclusters and Fe-doped Ni2P nanoparticles coexist on CeO2 nanorods.

[0072] pass Figure 3 It can be seen that the multi-active-site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nanoenzyme electrocatalyst exhibits a current density as high as 623.5 mA / cm² at a potential of -0.7 V vs. RHE. 2 As can be seen from Tables 1 and 2, the multi-active site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nanoenzyme electrocatalyst has a yield of 43.5 mg h⁻¹.-1 cm -2 The ammonia yield, ammonia Faradaic efficiency of 91.2%, and industrial-grade ammonia current density were all achieved. Furthermore, similar multi-active-site catalysts exhibited superior ammonia yield and Faradaic efficiency compared to single-phase catalysts, highlighting the advantages of this multi-active-site nanozyme structure in optimizing the adsorption of nitrogen-containing intermediates during nitrate-to-ammonia production. This is beneficial for accelerating the hydrogenation of nitrogen-containing intermediates to ammonia.

[0073] pass Figure 4 It can be seen that the multi-active-site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst can be stably cycled 16 times at a potential of -0.4V vs. RHE, achieving stable removal of nitrate while also producing ammonia.

[0074] pass Figure 5 It can be seen that the multi-active-site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst phase in 1.0 M KOH solution has a current of 50 mA / cm². 2 At current density, it exhibits a lower OER reaction overpotential of 288 mV compared to single-active-site catalytic materials and commercially available RuO2.

[0075] pass Figure 6 It can be seen that the multi-active-site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nanozyme electrocatalyst exhibited a maximum power density of 21.1 mW / cm³ in a mixed solution of 1.0 M KOH and 0.5 M KNO₃. 2 .

[0076] pass Figure 7 It can be seen that the multi-active-site Fe-Fe of the present invention x Ni 2-x The P / CeO2 biomimetic nano-enzyme electrocatalyst exhibits good charge-discharge cycle stability at 3 mA / cm². 2 It can operate stably for 8 hours at current density.

[0077] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical solution of the present invention, various simple modifications can be made to the synthesis scheme of the present invention, including but not limited to adjusting the proportion of each additive and combining various suitable methods. These modifications and combinations should be considered as the content disclosed in the present invention and all fall within the protection scope of the present invention.

Claims

1. An enzyme-mimicking Ce02-based multi-active-site catalyst, characterized in that: CeO2 nanorods supported X nanoclusters and X doped Ni2P nanoparticles, wherein X is Fe, Co, Cu or Mn.

2. The enzyme-mimicking CeO2-based multi-active-site catalyst of claim 1, wherein, The total mass of X is 0.1%-50% of CeO2; the mass of Ni2P is 0.1%-50% of CeO2.

3. A method for preparing an enzyme-mimicking CeO2-based multi-active site catalyst, characterized in that, The method comprises the following steps: Step 1: uniformly mixing cerium salt and ammonia water, obtaining CeO2 nanorods through one-step hydrothermal method, centrifugal cleaning, vacuum drying and air atmosphere heat treatment; Step 2: uniformly stirring aqueous solutions of X salt, nickel salt, reducing material and template material to obtain a mixed solution; wherein the X salt is iron salt, cobalt salt, copper salt or manganese salt; Step 3: adding the CeO2 nanorods obtained in step 1 into the mixed solution in step 2, anchoring metal ions on the CeO2 nanorods to form a precursor through strong interaction of metal carriers; Step 4: obtaining CeO2 nanorods supported X nanoclusters and X doped Ni2P nanoparticles through sodium hypophosphite phosphorization reaction of the precursor synthesized in step 3; Fe-Fe x Ni 2-x P / CeO2 biomimetic nanoszyme electrocatalyst or, when cobalt salt is used in step 2, Co-Co with multiple active sites of CeO2 nanorod supported Co nanoclusters and Co-doped Ni2P nanoparticles is obtained x Ni 2-x P / CeO2 biomimetic nanoszyme electrocatalyst; or, when the copper salt is used in step 2, Cu-Cu x Ni 2-x P / CeO2 biomimetic nanoszyme electrocatalyst or, when manganese salt is used in step 2, Mn-Mn x Ni 2-x P / CeO2 biomimetic nanoszyme electrocatalyst.

4. The method for preparing the enzyme-mimic CeO2-based multi-active-site catalyst according to claim 3, wherein, in the step 1, the cerium salt is at least one of nitrate, chloride or sulfate; and the synthesis of the CeO2 nanorods in step 1 is performed in an alkaline environment with pH=10-14. The temperature of the hydrothermal reaction is 100-200 degrees, and the duration is 5-30 hours; the air atmosphere heat treatment temperature is 300-700 degrees, and the duration is 1-10 hours. In step 2, the X salt and the nickel salt are at least one of nitrate, chloride or sulfate. The reducing material is at least one of sodium citrate, glucose, ethylene glycol or glycerol; and the template material is at least one of hexamethylenetetramine, polyvinylpyrrolidone or ethylenediamine. In step 4, the reaction temperature of the phosphorization reaction is 200-300 degrees, and the reaction time is 1-5 hours. The addition amount of the reducing material is 0.1%-50% of the cerium salt; and the addition amount of the template material is 1-10 times of the cerium salt.

5. The method for preparing the enzyme-mimicking CeO2-based multi-active-site catalyst according to claim 4, characterized in that, The addition amount of sodium hypophosphite is 1%-300% of cerium oxide; the addition amount of the nickel salt is 1-10 times of cerium oxide; and the addition amount of the X salt is 1%-300% of cerium oxide.

6. Use of the enzyme-mimic CeO2-based multi-active-site catalyst according to claim 1 or 2 as cathode material for electrolytic reduction of nitrate to produce ammonia.

7. Use of the enzyme-mimic CeO2-based multi-active-site catalyst according to claim 1 or 2 as anode material for alkaline electrolysis cell. The application comprises anode material, cathode material and reference electrode; the cathode material is the enzyme-mimic CeO2-based multi-active-site catalyst according to claim 1 or 2, the reference electrode is mercury / mercuric oxide electrode, and the anode material is Pt sheet.

8. A nitrate salt based electrolytic cell characterized in that, The application comprises anode material, cathode material and reference electrode; the anode material is the enzyme-mimic CeO2-based multi-active-site catalyst according to claim 1 or 2, the reference electrode is mercury / mercuric oxide electrode, and the cathode material is Pt sheet.

9. An alkaline electrolysis cell, characterized in that ​ 10. A zinc nitrate battery, characterized by, The application relates to a battery, which comprises a positive electrode material and a negative electrode material, wherein the positive electrode material is an enzyme-mimicking CeO2-based multi-active-site catalyst as claimed in claim 1 or 2, and the negative electrode material is zinc sheet.

Citation Information

Patent Citations

  • Modified CeO2 nanorod-doped catalyst and application thereof

    CN106492778A

  • Nickel phosphide nanoflower catalyst loaded with superfine CeO2 nanoparticles as well as preparation method and application of nickel phosphide nanoflower catalyst

    CN117380231A

Cited By

  • Ag-FeOOH electrocatalyst, hydrogel enhanced electrocatalytic electrode as well as preparation method and application of Ag-FeOOH electrocatalyst and hydrogel enhanced electrocatalytic electrode

    CN121781210A